Implications of Legal Problems for Police Efforts to Eradicate Online Gambling Crimes - Ratu Kenya W; Gunarto Gunarto (UNISSULA Semarang, 2025)
Abstract. Many online gambling operators are based overseas, making national jurisdictions inadequate for effective legal proceedings. Extradition processes, requests for mutual legal assistance (MLA), and international cooperation are essential, but their implementation is not always smooth due to differences in legal systems and political interests between countries. Therefore, the government and the police need to take effective steps to prevent and stop online gambling practices in society. Based on this situation, efforts to address the problem of online gambling require effective criminal law policies. The purpose of this study is to determine and analyze (1) the dynamics of online gambling in Indonesia from the perspectives of legal sociology and positive law, (2) current police efforts to eradicate online gambling crimes, and (3) legal issues hindering police efforts to eradicate online gambling crimes. The approach used in this study is normative juridical. The research specifications are descriptive and analytical. The data sources used are secondary data. Secondary data is data obtained from library research, consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The research results and discussion can be concluded as follows: (1) Legal sociology considers that in the public's view, it is necessary to improve legal doctrine so that the public can understand the dangerous and destructive impacts of online gambling as well as legal doctrine on the effectiveness of law enforcement against the sources of the increase in online gambling itself. Modernization of law against online gambling is applied to legal products in Law Number 1 of 2024 concerning Electronic Information and Transactions. (2) Technically, the Police eradicate online gambling in collaboration with the Ministry of Communication and Digital, one of the efforts carried out by the National Police's Cyber Crime Directorate is to carry out formal supervision through cyber patrol techniques. The main purpose of carrying out formal supervision is to create a deterrent effect on criminals because the risk of being caught is high. One implementation of this strategy is in the form of the Cyber Patrol method carried out by Sub-Directorate 3 of the Cyber Crime Directorate of the National Police's Criminal Investigation Agency. (3) The Police need support from the government in the form of formulations from a legal and foreign policy perspective to further legitimize Police actions in reaching online gambling crime subjects located abroad. In many cases, online gambling servers or perpetrators' social media accounts are based abroad. When the data and perpetrators are in different jurisdictions, Indonesian authorities must go through a lengthy international cooperation mechanism.